Unveiling the Dark: Exploring the Nomological Consistency of the Short Dark Triad and Dirty Dozen Scales - Marco Tommasi; Marco Lauriola; Aristide Saggino (Europe's Journal of Psychology, 2025)
We examined the consistency of the Short Dark Triad (SD3) and the Dirty Dozen (DD) scales, which are widely used for assessing Dark Triad traits (Machiavellianism, narcissism, and psychopathy), in a community Italian sample of 504 individuals aged 18 to 89 years. The findings revealed strong convergence for Machiavellianism and psychopathy across the two scales. In contrast, narcissism demonstrated weaker convergence, with moderate correlations between the SD3 and DD scales. Nomological consistency, the degree to which different indicators of a construct share similar associations with external criteria, was assessed using four sets of criteria: psychopathy or empathy, the Five-Factor Model of personality, mental health (psychological well-being, anxiety, and depression), and social disinhibition. Both scales showed moderate consistency with empathy, the Big Five, and social disinhibition criteria but displayed inconsistency concerning mental health criteria. Psychopathy and Machiavellianism exhibited distinct patterns in relation to social disinhibition. Narcissism demonstrated the most divergence from other traits and the highest inconsistency between SD3 and DD. The SD3 appeared to focus predominantly on grandiose narcissism, whereas the DD scale likely encompasses both grandiose and vulnerable aspects of narcissism. Consequently, SD3 and DD cannot be considered fully equivalent measures of Dark Triad traits.